2017
DOI: 10.1017/s095927091700017x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the system of protected areas of Lombardy (Northern Italy) in preserving breeding birds

Abstract: SummaryNetworks of protected areas (PAs) where human activities are allowed at different degrees are fundamental to ensure the long-term conservation of biological diversity and ecological processes. However, studies aimed at assessing their effectiveness, focusing on several species simultaneously are scarce. We assessed the effectiveness of the system of protected areas (PAs) of Lombardy, Northern Italy, in conserving bird populations by comparing the changes from 1992 to 2013 in the occurrence of 54 breedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…In conclusion, how can we promptly and effectively counteract the negative trend showed by edge and open habitat birds in mountain areas? The conservation of open mountain habitats (grassland and prairies) is strictly linked to local ad hoc management practices that should also be implemented through several economic activities (e.g., marketing of local typical products, recreational outdoor activities, and food services) that depend on open habitats, even within the wide system of protected areas of the Central Italian Alps (Sicurella et al, ). Of course, these for‐profit activities should be addressed toward sustainable forms by adequate governance policies, in order to maintain a viable mountain economy in the long‐term, which should also be perceived as an attractive employment opportunity and produce a positive and broader perception in terms of ecosystem services (Schermer et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, how can we promptly and effectively counteract the negative trend showed by edge and open habitat birds in mountain areas? The conservation of open mountain habitats (grassland and prairies) is strictly linked to local ad hoc management practices that should also be implemented through several economic activities (e.g., marketing of local typical products, recreational outdoor activities, and food services) that depend on open habitats, even within the wide system of protected areas of the Central Italian Alps (Sicurella et al, ). Of course, these for‐profit activities should be addressed toward sustainable forms by adequate governance policies, in order to maintain a viable mountain economy in the long‐term, which should also be perceived as an attractive employment opportunity and produce a positive and broader perception in terms of ecosystem services (Schermer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For each species showing a significant elevational range change, we assessed the association of each pattern of elevational range change with the (a) breeding habitat, (b) the migration habit, and (c) the range change driver. The breeding habitat (open, edge, or forest species) and migration habit (long‐distance migrant [ldm], short‐distance migrant [sdm] or resident [res]) were assigned according to Sicurella, Orioli, Pinoli, Ambrosini, and Bani () and integrated by the authors where necessary. The association between each pair of categorical variables was assessed performing a log‐linear analysis (Agresti, ) on the observed bird species’ frequencies from a contingency table obtained by crossing the pattern of elevational range change, the breeding habitat, the migration habit, and the drivers of range change.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an ongoing debate about whether agro-environmental management practices mainly benefit common species or if their effects favor rare and declining species (Sicurella et al 2018). Castro-Caro et al (2014a showed that, in olive groves in southern Spain, the presence of herbaceous cover and hedges had a positive effect on two birds with unfavorable conservation status (BirdLife International 2004), the Rufous-tailed Scrub-Robin Cercotrichas galactotes and the Woodchat Shrike Lanius senator, classified respectively as endangered (EN) and Vulnerable (VU) in Spain (Madroño et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This information can be used in conservation practices aimed at enhancing species richness in those urban landscapes where other options (e.g., extension of the size patches, creation of other proximate UPUFs) are not as feasible. Of course, this last result can be, in part, explained by considering that when reserves are designed they are usually located in areas characterized by more suitable habitats [65] where maintenance of biodiversity is favoured [66].…”
Section: Temporal Changes Of the Effect Of Upufs Characteristics On Bmentioning
confidence: 99%